Implementasi Kebijakan Pengelolaan Sampah melalui Program Bank Sampah di Kelurahan Tegalsari Kota Surabaya - Perbawaningati, Hanugrah Zain; Ayu, Sigi Jenar Mahesa; Ramadhani, Fihaqi Izza Aldin; Ali, Mohammad (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
The increasing volume of waste in Surabaya City is inseparable from population growth and high economic activity, so that effective management solutions are needed, one of which is through community-based programs such as the Waste Bank. The purpose of this study is to analyze how the Waste Bank program in Tegalsari Village is implemented and what factors contribute to its success, based on the policy implementation theory of George C. Edwards III. This study uses a qualitative method with a case study approach, collecting primary data through in-depth interviews and secondary data sourced from related official documentation. The research findings show that the Waste Bank program has been implemented well and is in line with the factors in the policy implementation theory of George C. Edwards III, particularly in the aspects of communication, disposition, and bureaucratic structure, although there are still obstacles in the aspect of resources due to the uneven distribution of facilitation assistance from the government. Overall, the success of this program rests on the commitment of the managers, community participation, and cooperation with the private sector, but on the other hand it also requires improvements in terms of coordination and information transparency regarding government support so that waste management can run better and continue sustainably. Keyword : policy implementation, waste banks, community participation